Fabrication of AC@ZSM‐5 core‐shell particles and their performance in Fischer–Tropsch synthesis. Issue 12 (15th April 2013) - Chen, Fengqiu; Jin, Weiyang; Cheng, Dang‐guo; Zhan, Xiaoli; Lin, Y.S.
Abstract: Background: Because of its rough surface and the hydrophobic property of porous activated carbon (AC) particles, it is more difficult to grow a zeolite layer on an AC surface than on metal oxides. The aim of the present study is the in situ hydrothermal synthesis of continuous ZSM‐5 zeolite layer encapsulated porous AC particles (AC@ZSM‐5) through an alumina intermediate layer strategy. To evaluate the effects of the zeolite layer on its catalytic application, active species (Co and Zr) were introduced into the AC and used for Fischer–Tropsch synthesis . Results: A continuous zeolite layer cannot be formed on the surface of the irregular AC particles, even when pretreated by air oxidation or concentrated nitric acid, but can be synthesized using the alumina intermediate layer method. A catalytic test of CoZr/AC@ZSM‐5 indicates that the zeolite layer shell has a marked effect on product distributions . Conclusion: Aided by the alumina intermediate layer, zeolite crystals nucleate at the support/solution interface rather than in solution. For Fischer–Tropsch synthesis over CoZr/AC@ZSM‐5, the product distributions are shifted to methane and light hydrocarbon compared with that of CoZr/AC. © 2013 Society of Chemical Industry